Mali : Poverty Reduction Strategy Paper; Implementation Report for 2003 and 2004; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
This Joint Staff Advisory Note discusses key findings of the Implementation Report for 2003 and 2004 of the Poverty Reduction Strategy Paper for Mali. With real GDP growth averaging 5 percent over the period 2003-05, Mali's growth performance has improved over the preceding three years, although growth has fallen short of the Poverty Reduction Strategy Framework goal. The IMF staff agrees that this underperformance can be explained both by adverse external and natural shocks and the authorities' 'optimistic and voluntaristic' growth objectives that represent a best-case scenario.